2018
DOI: 10.1039/c8sc00961a
|View full text |Cite
|
Sign up to set email alerts
|

A porous, electrically conductive hexa-zirconium(iv) metal–organic framework

Abstract: Electrical conductivity is engendered in a pyrene containing hexa-zirconium(iv) metal–organic framework by physically encapsulating fullerenes within MOF cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
144
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 59 publications
11
144
0
5
Order By: Relevance
“…To further elaborate on the observed changes in the XPS spectra, we performed conductivity measurements demonstrating that, for instance, the conductivity of NEM‐C 60 [ 1≡(34 %) ] was found to be 1.97×10 −6 S cm −1 in comparison with the parent COF (2.32×10 −12 S cm −1 ) . Our observations that conductivity increases with promotion of donor–acceptor alignments are in line with literature reports . On the example of TCNQ‐integrated materials, we also studied changes in electronic properties as a function of the degree of acceptor integration.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…To further elaborate on the observed changes in the XPS spectra, we performed conductivity measurements demonstrating that, for instance, the conductivity of NEM‐C 60 [ 1≡(34 %) ] was found to be 1.97×10 −6 S cm −1 in comparison with the parent COF (2.32×10 −12 S cm −1 ) . Our observations that conductivity increases with promotion of donor–acceptor alignments are in line with literature reports . On the example of TCNQ‐integrated materials, we also studied changes in electronic properties as a function of the degree of acceptor integration.…”
Section: Resultssupporting
confidence: 81%
“…We probed charge transfer rates within the Marcus theory as a function of acceptor stacking. Furthermore, we estimated redox behavior using cyclic voltammetry of pure organic crystalline porous scaffolds containing covalently decorated pores with strong electron accepting bound tetracyanoquinodimethane (TCNQ) and fullerene (C 60 ) moieties, which are the first studies of this kind reported for any buckyball‐ or TCNQ‐integrated COFs to date (Scheme ). We demonstrate that the concept of fluorophore tag integration could be an effective avenue to monitor reaction progress inside of a COF.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Die gleiche Te ndenz wurde füro rganische Porphyrin-Fulleren-Schichten vorhergesagt [24] und experimentell nachgewiesen. Hier beträgt das elektronische Kopplungselement der LUMO-Orbitale 0.33 meV,steigt aber bei abnehmendem intermolekularem Fullerenabstand deutlich an.…”
Section: Angewandte Chemieunclassified
“…[1] In den letzten Jahren haben neben Anwendungen in der Gasbeladung und -trennung [2] auch die elektrischen und elektronischen Eigenschaften von MOFs zunehmend an Bedeutung gewonnen. Es wurde festgestellt, dass die Leitfähigkeit von MOF-Materialien durch Beladung mit Molekülen wie Ferrocen, [3c] Te tracyanchinodimethan [3b] oder C 60 -Fullerenen [8] signifikant verbessert werden kann. Es wurde festgestellt, dass die Leitfähigkeit von MOF-Materialien durch Beladung mit Molekülen wie Ferrocen, [3c] Te tracyanchinodimethan [3b] oder C 60 -Fullerenen [8] signifikant verbessert werden kann.…”
unclassified
See 1 more Smart Citation